An Assessment of Radioactivity Levels of Radionuclides for Surface and Deep Soils Yathrib district, Balad district, Salah al-Din Governorate /Iraq (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: In this study, the radioactivity levels of the naturally occurring radionuclides represented with uranium , thorium , and isotope of potassium . As well as calculating the radiation risk indicators of Gamma rays represented by (the activity of the equivalent radium Raeq, the risk index for the gamma rays Iγ and the rate of the absorbed dose in the air (Dγ). Surface and deep soil models (60cm), which were collected from twelve sites in Yathrib sub-district of Balad in Salah al-Din Governorate - Iraq.  ranged between (AD3(2.84) - AD5(105.88) Bq/Kg) and  for actinium Bq/Kg  ((AD6(6.42) - AD11(43)  and for potassium    (AD6(8.03) -AD5(78.72)) Bq/Kg) for deep soil models (60cm) for radium  ranged between (AD12 (9.96) -AD11 (31.3) Bq / Kg) and for actinium  Bq / Kg) (AD10 (0.49) -AD3 (16.31) (and for potassium  Bq / Kg) (AD9 (8.03) - AD6 (28.12).As for the results of the rate of radiation hazard effects for gamma rays for surface soil models where the equivalent radium activity rate is Raeq (Bq / kg 53.64 AD1 (AD8 (13.25) -), while the risk index ratio for gamma rays is IgBq / kg) (0.36AD1 (AD8)). (0.094) -), and the average absorbed dose in the air Dg (nGy / h) 20.15 (AD11 (AD8) 5.94) -. For 60cm deep soil models, the equivalent radium activity rate is Raeq Bq / kg (48.33 (AD3)). AD10 (16.81) -, the hazard index for gamma rays Ig (Bq / kg) 0.333 (AD3 AD10 (0.114) -), and the dose absorbed in air Dg (nGy / h 21.87) (AD3 (AD10) 7.31) In general, the results showed that the concentration of radionuclides in the surface soil is higher than that of the deep soil.